2023
DOI: 10.1002/cjp2.317
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutations and endometriosis burden of disease

Abstract: The clinical phenotype of somatic mutations in endometriosis is unknown. The objective was to determine whether somatic KRAS mutations were associated with greater disease burden in endometriosis (i.e. more severe subtypes and higher stage). This prospective longitudinal cohort study included 122 subjects undergoing endometriosis surgery at a tertiary referral center between 2013 and 2017, with 5–9 years of follow‐up. Somatic activating KRAS codon 12 mutations were detected in endometriosis lesions using dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is reported that KRAS mutation is associated with greater anatomic disease burden and surgical complexity. Their results showed KRAS mutation is not associated with pain, but efficacy of progestin on pain is not assessed [70]. To the best of our knowledge, the mechanisms underlying KRAS mutation-associated progesterone resistance in PGE2 synthesis or pain in endometriotic epithelial cells are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that KRAS mutation is associated with greater anatomic disease burden and surgical complexity. Their results showed KRAS mutation is not associated with pain, but efficacy of progestin on pain is not assessed [70]. To the best of our knowledge, the mechanisms underlying KRAS mutation-associated progesterone resistance in PGE2 synthesis or pain in endometriotic epithelial cells are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA and KRAS mutations have been demonstrated to be clonally expanded in endometriosis [ 53 ]. KRAS codon 12-activating mutations have been shown to be associated with the proliferation, local invasion, and metastatic spread of endometriosis and large disease burden resulting in advanced-stage disease with increased surgical complexity [ 54 ]. The RAS/RAF/MEK (MAPK, mitogen-activated protein kinase) signaling pathway may therefore be a relevant target to reduce the invasiveness, spread, or burden of endometriosis.…”
Section: Methodsmentioning
confidence: 99%
“…Linked clinical data from the patient were available from a prospective registry as described previously (H16-00264; Clinicaltrials.gov NCT02911090), ( 13 ) which included standardized surgeon-reported data at the time of surgery. This cohort has been described previously ( 14 ). For each tissue block from each patient included in the study, a tissue slide was cut for H&E and histological endometriosis was confirmed.…”
Section: Methodsmentioning
confidence: 99%